Geotechnical properties and foundation requirements for the Satellite and Lunar Laser Ranger at the Matjiesfontein Space Geodesy Observatory - Bothma, Susan (Stellenbosch : Stellenbosch University, 2015)
Thesis (MEng)--Stellenbosch University, 2015.